Suplementación proteica para el mantenimiento y fortalecimiento proteico a las colmenas de abejas (apis mellifera) recinto aguas frías - cantón Mocache. - Avilez Rendon, Yojaira Elizabeth (2022)
vii ABSTRACT The present study was carried out in the cold water precinct of the Mocache Canton, with the objective of evaluating the effect of protein supplementation (16-19-22-25%) on Bee colonies (Apis mellifera.), Where 16 beehives were evaluated. bees, the variables to study were; population status, food consumption, incidences of diseases and cost of treatments, where a completely random design was used with four treatments and four repetitions (each experimental unit was constituted by a hive), all the treatments were supplied in the form of cake where the ingredients were: dry and ground pollen, sugar, soybean and honey flour (T1), pollen, sugar, soy and honey flour (T2), brewer’s yeast, sugar, soybean meal and honey (T3) , pollen, sugar, soybean meal and honey (T4).